Association of per-and polyfluoroalkyl substances with thyroid hormones in the umbilical cord blood of neonates born by spontaneous delivery - Song, Yubo; Du, Wei; Hu, Jufeng (Frontiers in Public Health, 2025)
ObjectivePer-and polyfluoroalkyl substances (PFASs) affect thyroid function, impairing neonatal development and growth. This study aims to explore the association between PFASs and thyroid hormones in the umbilical cord blood of neonates delivered spontaneously.MethodsA total of 119 puerperae who delivered vaginally were included. Twenty-nine PFASs were quantified in the umbilical cord plasma using a Waters ACQUITY ultra-performance liquid chromatography (UPLC) system coupled with a Waters Quattro Premier XE triple quadrupole mass spectrometer. Five thyroid hormones were quantified in umbilical cord plasma using a Roche Analytics E170 modular analyzer.ResultsPerfluorooctanoic acid (PFOA), 6:2 chlorinated polyfluorinated ether sulfonic acid (6:2 Cl-PFESA), and linear perfluorooctane sulfonic acid (L-PFOS) were present in the highest levels in the umbilical cord blood with median (quartile 1–quartile 3) levels of 3.23 (2.32–4.32), 1.35 (0.84–2.01), and 0.94 (0.63–1.41) ng/mL, respectively. The linear regression analysis revealed that linear perfluorohexane sulfonic acid (L-PFHxS) (β = 0.557, p = 0.038) and perfluorononanoic acid (PFNA) (β = 0.613, p = 0.045) were independently and positively associated with free triiodothyronine (T3), but PFOA exhibited an inverse trend (β = −0.040, p = 0.002). The sum of 3,4,5 monohydroperfluorooctane sulfonates (Σ3,4,5 m-PFOS) was independently and negatively associated with total T3 (β = −0.349, p = 0.007). Perfluorododecanoic acid (PFDoA) was found to have a positively correlation with total T3 (β = 2.107, p = 0.027) and free T3 (β = 5.254, p = 0.008).ConclusionL-PFHxS, PFNA, PFOA, Σ3,4,5 m-PFOS, and PFDoA are associated with thyroid hormones in the umbilical cord blood of neonates delivered spontaneously.